Monoclonal antibodies to hepatitis B surface antigen: production and characterization - Hlozánek, I; Dostálová, V; Korec, E; Zelený, V; König, J; Nĕmecek, V (Folia biologica, 1986)
Hybridomas secreting anti-HBsAg antibodies were produced by fusion of the mouse myeloma cell line SP2/0 with lymphocytes from mice immunized with purified HBsAg. All clones produced antibodies of the IgG1 idiotype that react with the subtype a determinant of HBsAg. An enzyme immunoassay for detection of HBsAg in human sera using monoclonal antibodies was developed and compared with commercial Sevatest ELISA HBsAg/micro I kit for detection of HBsAg in clinical serum samples.
Keywords: ELISA; hepatitida B - antigeny povrchové; Hepatitis B Surface Antigens; myši; Immunoenzyme Techniques; Immunoglobulin G; monoklonální protilátky; Antibodies, Monoclonal; Animals; imunoglobulin G; Enzyme-Linked Immunosorbent Assay; Hepatitis B Antibodies; Mice; imunoenzymatické techniky; hepatitida B - protilátky; zvířata